WAYS TO IMPROVE THE MONETARY POLICY IN UZBEKISTAN (Conferencea, 2022)
Improving the standard of living of the population today remains the main goal of the socio-economic policy of all modern societies. It should be noted here that the most important aspect of prosperity is undoubtedly economic growth.